Can Countries Establish Sovereignty over the Internet?. (2nd July 2016) - Amemiya, Kanji
Abstract : While the Internet is now a component of people's everyday lives and is becoming more and more convenient, it has also brought about various problems and adverse effects that could be damaging to human rights, corporate interests, and even national interests. In order to address these problems and adverse effects, countries have recently begun to establish national boundaries over the Internet to control it. This article will consider whether countries are capable of establishing sovereignty over the Internet. To this end, first the scope of national sovereignty in terms of the physical entities that make up Internet services, namely, providers, users, network equipment, and network facilities will be defined. Then the four methods for establishing national sovereignty over the Internet from the perspective of social phenomena will be examined. In addition, in examining whether it is possible for countries to secure the power to levy taxes over the Internet, the article will consider the requirements for countries to establish sovereignty over the Internet. Finally, an explanation and attempt to elucidate a new phenomenon involving the movement of corporate earnings to the cloud will be offered.